Factors of Development of the Sugar Industry - Kondrakiewicz, Teresa (Regional Barometer. Analyses & Prognoses, 2008)
The article discusses the factors of development of the sugar industry. Poland is a significant producer of sugar in Europe. Sugar industry plays an important role in Polish economy. Financial situation of the sugar industry changes quite often, which leads to a question about the minor factors of development of the sugar industry. There are two groups of these factors. The first one includes the factors connected with the market situation on the world sugar market and the level of demand. The second group of factors came into being as a result of specific situation on the sugar industry: its high dependence on agriculture and the fact that it is adjusted to Common Agriculture Policy. Since the season 2006/2007 a reform of the sugar market has been carrying through. Some of its aspects are the reduction of production limits, which have led to close many sugar factories, and the fall of sugar prices. The purpose of this reform is to improve the competitiveness of the European Union sugar industry on the world market.